2020
DOI: 10.1093/ajcp/aqaa152
|View full text |Cite
|
Sign up to set email alerts
|

Coping With COVID-19

Abstract: Objectives The first coronavirus disease 2019 (COVID-19) case in the United States was reported in Washington State. The pandemic caused drastic disruptions to medical institutions, including medical education. The Department of Laboratory Medicine at the University of Washington responded by rapidly implementing substantial changes to medical student clerkships. Methods In real time, we converted one ongoing case- and didact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
0
16
0
5
Order By: Relevance
“…Similar to the University of Minnesota, pathology departments across the world have converted the crisis of the COVID-19 pandemic to an opportunity for developing their own virtual electives in both AP and CP. [16][17][18] Additionally, the online resource "PathElective" developed at Loyola University Chicago Stritch School of Medicine provides a comprehensive and free elective for medical students to learn pathology from world-renowned pathologists in a virtual format. 19 This virtual space offers students access to learn from pathologists in a variety of settings, network with different pathology departments, and collaborate globally with other interested medical students.…”
Section: Consmentioning
confidence: 99%
“…Similar to the University of Minnesota, pathology departments across the world have converted the crisis of the COVID-19 pandemic to an opportunity for developing their own virtual electives in both AP and CP. [16][17][18] Additionally, the online resource "PathElective" developed at Loyola University Chicago Stritch School of Medicine provides a comprehensive and free elective for medical students to learn pathology from world-renowned pathologists in a virtual format. 19 This virtual space offers students access to learn from pathologists in a variety of settings, network with different pathology departments, and collaborate globally with other interested medical students.…”
Section: Consmentioning
confidence: 99%
“…Medical school administrators looked for ways to fill this gap. Some institutions created ways to integrate medical students into clinical work, even though they were not physically present in the hospital [ 2 - 8 ]. With the incorporation of video conferencing platforms into patient care, some students cared for patients virtually, including remote observation and communication with patients and family members [ 9 ].…”
Section: Background/rationalementioning
confidence: 99%
“…Digital disengagement, increased susceptibility to distractions, and teleconferencing fatigue have been noted by others. 4 - 6 Hassell et al conducted an online survey of pathology trainees, program directors, and faculty to assess pre- and post-COVID-19 use of, and response to, various digital pathology modalities and found that a majority of faculty and learners assessed that this shift had adversely affected the quality and effectiveness of teaching. 4 …”
Section: Graduate Medical Education Programsmentioning
confidence: 99%